Forage Production of Sorghum Cultivars - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
Total production from three cuttings of eight hay-type sorghum entries was greater from ‘Sweet Sioux WMR,’ ‘Cadan 99B,’ and ‘Trudan Headless’ than from ‘SDH 2942BMR’ and ‘AS6402.’ A separate test of 15 forage sorghums was conducted to assess dry matter (DM) production and other characteristics. Yields of ‘SPX-28313’ and ‘1990’ exceeded yields of 11 other entries. Production of ‘SPX3952,’ ‘AF7102,’ and ‘Atlas’ was less than that of six of the higher-yielding entries. Sorghum production tests were also conducted at Ottawa and Hutchinson (see KAES Research Reports, Vol. 1, Issue 2,Kansas Field Research).
Keywords: sudangrasses; ensilage; hay; maturity; lodging